MODELING OF INFORMATION TECHNOLOGY OF MATERIAL RESOURCES MANAGEMENT OF A CONSTRUCTION COMPANY - Maryna Novozhylova; Vladyslav Kramarenko; Olga Chub (Сучасний стан наукових досліджень та технологій в промисловості)
The article's research subject is the information technology of construction company's material resources management. The work's purpose is to construct and implement tools for modeling construction company's material resources management information technology. The article solves the following tasks: determining the place of information technology of construction company's material resources management in the modern construction company's information ecosystem, defining the main components, and building a functional model of construction company's material resources management information technology, taking into account the shortcomings of existing models, сreation of the multicriteria optimization model of the considered information technology. The following methods are used: system analysis, structural analysis, mathematical modeling of complex systems and processes, multicriteria optimization. The following results were obtained: a structural analysis of the existing information ecosystem at the regional level construction company, the composition of which is agreed on the organizational structure elements of the enterprise and the stages of the construction life cycle; considered the functions of construction company's material resources management which are realized at various stages of a construction project life cycle; constructed the set-theoretical model of material resources management information technology; determined the functional characteristics of the considered information technology, offered the criteria of information technology efficiency according to the ITIL strategy; constructed the conceptual model of information technology of material resources management. Conclusions: for the first time, developed tools for modeling construction company's material resources management information technology, including a theoretical-multiple model of material resources management information technology; Offered the information technology's conceptual scheme which realizes specific information technology's functional characteristics. The built modeling strategy will provide an opportunity for further development and software implementation of the information technology.